2009
DOI: 10.1016/j.jtcvs.2008.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Repair-oriented classification of aortic insufficiency: Impact on surgical techniques and clinical outcomes

Abstract: Aortic valve repair is an acceptable therapeutic option for patients with aortic insufficiency. This functional classification allows a systematic approach to the repair of Al and can help to predict the surgical techniques required as well as the durability of repair. Restrictive cusp motion (type III), due to fibrosis or calcification, is an important predictor for recurrent Al following AV repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 310 publications
(206 citation statements)
references
References 14 publications
5
181
0
7
Order By: Relevance
“…As the AV apparatus dilates, or when there is prolapse of a cusp, the ability for the aortic cusps to coapt decreases, resulting in AI. 6 Results of our study showed that the CoapSA in patients with AI also decreases significantly, which intuitively makes perfect sense. A second important application of this technique is in the immediate postoperative evaluation of AV repair.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As the AV apparatus dilates, or when there is prolapse of a cusp, the ability for the aortic cusps to coapt decreases, resulting in AI. 6 Results of our study showed that the CoapSA in patients with AI also decreases significantly, which intuitively makes perfect sense. A second important application of this technique is in the immediate postoperative evaluation of AV repair.…”
Section: Discussionsupporting
confidence: 60%
“…The valves in these patients are defined in the surgical literature as type 1a, 1b, or 1c. 6 The mechanism of AI was found to be type 1a (dilatation of the sinotubular junction [STJ]) in five patients and type 1b (aortic root and STJ dilatation) in five patients. Associated cusp prolapse (type 2) was also found in one of the patients with type 1a disease and in three of the patients with type 1b disease.…”
Section: Study Populationmentioning
confidence: 99%
“…While the Carpentier classification for mitral valve regurgitation has seen widespread application, in recent years, a similar functional classification system for aortic regurgitation has been developed by El Khoury and colleagues [8]. In this system, the aortic valve is viewed as two components, the annulus and valve leaflets, the former consisting of the ventriculo-aortic junction and the sinotubular junction.…”
Section: Classification Of Aortic Regurgitationmentioning
confidence: 99%
“…prolapse) or III) restriction in leaflet motion such as that in bicuspid, rheumatic and other degenerative processes. One or more of these lesions may be present in to a given case of aortic regurgitation [8].…”
Section: Classification Of Aortic Regurgitationmentioning
confidence: 99%
See 1 more Smart Citation